Drought tolerance is associated with rooting depth and stomatal control of water use in clones of Coffea canephora - Pinheiro, H. A.; DaMatta, F. M.; Chaves, ARM; Loureiro, M. E.; Ducatti, C. (Oxford University Press, 2005)
center dot Background and Aims Drought is a major environmental constraint affecting growth and production of Coffea canephora. Selection of C. canephora clones has been largely empirical as little is known about how clones respond physiologically to drought. Using clones previously shown to differ in drought tolerance, this study aimed to identify the extent of variation of water use and the mechanisms responsible, particularly those associated morphological traits.center dot Methods Clones (14 and 120, drought-tolerant; 46 and 109A, drought-sensitive, based on their abilities to yield under drought) were grown in 120-L pots until they were 12-months old, when an irrigation and a drought treatment were applied; plants were droughted until the pressure potential (Psi(x)) before dawn (pre-dawn) reached -3.0 MPa. Throughout the drought period, Psi(x) and stomatal conductance (g(s)) were measured. At the end of the experiment, carbon isotope ratio and parameters from pressure-volume curves were estimated. Morphological traits were also assessed.center dot Key Results and Conclusions With irrigation, plant hydraulic conductance (K-L), midday Psi(x) and total biomass were all greater in clones 109A and 120 than in the other clones. Root mass to leaf area ratio was larger in clone 109A than in the others, whereas rooting depth was greater in drought-tolerant than in drought-sensitive clones. Predawn Psi(x) of -3.0 MPa was reached fastest by 109A, followed progressively by clones 46, 120 and 14. Decreases in g(s) with declining Psi(x), or increasing evaporative demand, were similar for clones 14, 46, and 120, but lower in 109A. Carbon isotope ratio increased under drought; however, it was lower in 109A than in other clones. For all clones, Psi(x), g(s) and KL recovered rapidly following re-watering. Differences in root depth, KL and stomatal control of water use, but not osmotic or elastic adjustments, largely explained the differences in relative tolerance to drought stress of clones 14 and 120 compared with clones 46 and 109A.
Keywords: carbon isotope ratio; elastic and osmotic adjustments; robusta coffee; vapour pressure deficit; water potential; water relations; water-use efficiency